Considering risks when using information technology - Diachenko, V. (Економічний вісник Донбасу, 2024)
The article examines risks and threats when using information and communication technologies. The purpose of the study is to identify the main types of risks and threats when storing data in the cloud. To achieve this goal, a set of measures to form the foundations of cybersecurity has been identified. It is emphasized that, taking into account today's challenges, not only cyber literacy of information and communication technology users is required, but also coordination and reorientation of research in the field of computer development, because new generations of software and hardware must guarantee the security of activities and compliance with the principle of confidentiality of private, business or state information. The methodological aspects of the study take into account the concept of identifying patterns of the emergence of new risks and threats to information and cyber security in modern conditions of rapid development of information technologies. The work used a set of interrelated scientific methods, in particular: dialectical, comparative analysis and logical when studying the essence of threats to information security in modern conditions of uncertainty and risk; empirical research method when comparing the features of the provision of cloud services by IT services; systematic approach when identifying a set of measures to form the foundations of cybersecurity. The scientific novelty lies in an integrated approach to studying the essence of risks and threats to information and cyber security in the context of the rapid development of information and communication technologies and when using cloud services. As a result of the theoretical study, risks and threats to cyber security were identified. It is emphasized that the operational identification of new types of threats and risks, the determination of their key characteristics will contribute to the delineation of their essential properties, the development of algorithms for their analysis and methods for managing them.